2008
DOI: 10.1007/s00420-008-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Occupational styrene exposure and hearing loss: a cohort study with repeated measurements

Abstract: This study found, that chronic and intensive styrene exposure increases the hearing thresholds. At levels of about 30-50 ppm as an average inhaled styrene per work day over a period of about 15 years with higher exposure levels above 50 ppm in the past, an elevated risk for impaired hearing thresholds can be expected. The formerly published results on ototoxic effects below 20 ppm could not be confirmed. With few exceptions (at frequencies of 1,000 and 1,500 Hz) no dose-response relationship between threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 41 publications
1
59
0
1
Order By: Relevance
“…The auditory thresholds for high frequency PTA were statistically different for groups with prolonged exposure to styrene levels within recommended limits (8 -12.5 kHz) 22 .…”
Section: Styrenementioning
confidence: 80%
See 2 more Smart Citations
“…The auditory thresholds for high frequency PTA were statistically different for groups with prolonged exposure to styrene levels within recommended limits (8 -12.5 kHz) 22 .…”
Section: Styrenementioning
confidence: 80%
“…The worst PTA responses for a wide range of frequencies (0.25 -8 kHz) were found among individuals of the group exposed to the solvent [22][23][24] .…”
Section: Styrenementioning
confidence: 92%
See 1 more Smart Citation
“…These differences can be attributed to the effects of the styrene exposure only, as possible confounding effects of noise exposure can be excluded because workers were exposed to noise levels well below the action level of 85 dBA set by the Occupational Safety & Health Administration. Many studies in literature investigated effects of organic solvents (such as styrene) on hearing functionality, but only in few cases these effects have been evaluated using OAEs [7,22,23]. It is not possible to make a direct comparison of our results with those obtained in these last studies because of differences in mixture of organic solvents to which workers are exposed, levels of exposure, and confound effects due to combined noise exposure.…”
Section: Discussionmentioning
confidence: 93%
“…In [23], authors found that at average inhaled styrene levels of about 30-50 ppm per working day over a period of about 15 years with previous exposure to higher levels above 50 ppm increased the risk for hearing impairment, but no relationship was found between parameters extracted from TEOAEs and level of exposure.…”
Section: Discussionmentioning
confidence: 99%